Aspects of style in the novels of Henry Fielding - Bock, Mary Stewart (Department of English Language and Literature, 2016)
The prefatory essays in Fielding's two major novels Joseph Andrews and Tom Jones foreground his interest in the problems and challenges of the writing of fiction. In the narrative, he experiments with answers to the questions raised in these discursive sections. Analysis of style in these novels also shows a gradual development from the pervasive and self-reflexive irony and the interplay of stylistic modes that characterise the earlier novel to the more confident and increasingly serious authorial voice of the latter. Both Fielding's theoretical concerns and the development in his narrative style help to situate him in relation to eighteenth-century debates about language and the nature of fiction. This thesis attempts to show that appropriate stylistic analysis can reveal connections between the syntactic patterns in the text and the underlying assumptions and broader concerns of the writer. As the first chapter will indicate, the term 'stylistic analysis' covers widely divergent practices proceeding from equally divergent assumptions about the proper scope of stylistics. My a priori assumption is that the literary text is an instance of discourse, of language in use in a communicative situation. Since no single model of discourse analysis is adequate to describe all aspects of literary style, I have drawn from different analytical approaches to illuminate different aspects of Fielding's prose. For the analysis of the rhetorical and expressive values of his syntax, the most productive approach has been the 'functionalist' stylistics of by M.A.K. Halliday, complemented by Roman Jakobson's theory of the poetic function of language. But neither of these approaches is adequate to deal with the specific challenge to the analyst of language in the novel: the diversity of styles and registers that are available to the novelist. Mikhail Bakhtin's theory of novelistic style as 'dialogical' or multi-voiced accommodates the diversity in Fielding's prose and affords insights into both the social-ideological resonances and the artistic function of the language of the texts.